The forgotten room [compact disc, unabridged] : a novel - Child, Lincoln (Child, Lincoln. Jeremy Logan series., 2015)
Jeremy Logan finds himself on the storied coastline of Newport, Rhode Island, where he has been retained by Lux, one of the oldest and most respected think tanks in America. Just days earlier, a series of frightening events took place in the sprawling seaside mansion that houses the organization. One of its most distinguished doctors began acting erratically, violently attacking an assistant in the mansion's library and, moments later, killing himself in a truly shocking fashion.